2012
DOI: 10.1080/14786419.2012.746338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying conditions on the quality ofOriganum syriacumL.

Abstract: The temperature and the speed of drying may affect the quality of the end product of medicinal plants. In addition, ecotypes and chemotypes could be factors influencing this quality. Thus, the aim of our study was to explore various techniques of drying of Origanum syriacum L., which is considered as a main ingredient in the Lebanese diet. For all these reasons, we decided to study two types of O. syriacum originating from Rkai and Ibrine regions on which analyses were carried out. In view of our results, a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Drying temperature had critical effect on chlorophyll and carotenoids contents of O. syriacum. High drying temperature led to higher destruction chlorophyll and carotenoids contents in comparison to low drying temperature [8].…”
Section: Introductionmentioning
confidence: 88%
“…Drying temperature had critical effect on chlorophyll and carotenoids contents of O. syriacum. High drying temperature led to higher destruction chlorophyll and carotenoids contents in comparison to low drying temperature [8].…”
Section: Introductionmentioning
confidence: 88%
“…Once drying of za’atar is achieved, it can be stored for several months if the storage area is dry and isolated from moisture, sunlight, heat, and polluting substances. Dried za’atar can be manually or mechanically threshed [ 18 ]. Za’atar grinding is the next step after threshing and sieving dried flowers and leaves to further mix with other ingredients to produce the za’atar mix.…”
Section: Production Of Za’atar MIXmentioning
confidence: 99%
“…Another study found that drying at a lower temperature was better for preserving chlorophyll and carotenoids contents in O. syriacum, while drying at a higher temperature produced O. syriacum with higher phenols content. It was also reported that shade drying at lower air velocity was the best for preserving alpha-tocopherol content [ 18 ]. Every processing method has its strengths and weaknesses, and every quality trait in za’atar responds differently to processing conditions.…”
Section: Production Of Za’atar MIXmentioning
confidence: 99%
See 2 more Smart Citations